Inhibition of EGFR and MEK surmounts entrectinib resistance in a brain metastasis model of NTRK1‐rearranged tumor cells. Issue 7 (11th May 2022) - Suzuki, Chiaki; Nishiyama, Akihiro; Arai, Sachiko; Tange, Shoichiro; Tajima, Atsushi; Tanimoto, Azusa; Fukuda, Koji; Takumi, Yohei; Kotani, Hiroshi; Takeuchi, Shinji; Yanagimura, Naohiro; Ohtsubo, Koushiro; et al.
Abstract: Tropomyosin receptor kinase (TRK) inhibitors have demonstrated histology‐agnostic efficacy in patients with neurotrophic receptor tyrosine kinase ( NTRK ) gene fusion. Although responses to TRK inhibitors can be dramatic and durable, duration of response may eventually be limited by acquired resistance via several mechanisms, including resistance mutations such as NTRK1 ‐G595R. Repotrectinib is a second‐generation TRK inhibitor, which is active against NTRK1 ‐G595R. However, its efficacy against entrectinib‐resistant tumors has not been fully elucidated. In the present study, we established entrectinib‐resistant tumor cells (M3B) in a brain metastasis model inoculated with NTRK1 ‐rearranged KM12SM cells and examined the sensitivity of M3B cells to repotrectinib. While M3B cells harbored the NTRK1 ‐G595R mutation, they were unexpectedly resistant to repotrectinib. The resistance was due to extracellular signal–regulated kinase (ERK) reactivation partially mediated by epidermal growth factor receptor (EGFR) activation. We further demonstrate that the triplet combination of repotrectinib, EGFR inhibitor, and MEK inhibitor could sensitize M3B cells in vitro as well as in a brain metastasis model. These results indicate that resistant mutations, such as NTRK1 ‐G595R, and alternative pathway activation, such as ERK activation, could simultaneously occur in entrectinib‐resistant tumors, thereby causing resistance to second‐generation inhibitor repotrectinib. These findings highlight the importance of intensive examinations to identify resistance mechanisms and application of the appropriate combination treatment to circumvent the resistance. Abstract : We explored the resistance mechanism to tropomyosin receptor kinase (TRK) inhibitors. We demonstrated that resistant mutations, such as NTRK1‐G595R, and alternative pathway activation, such as ERK activation, could simultaneously occur in entrectinib‐resistant tumors, thereby causing resistance to entrectinib as well as repotrectinib, and that this resistance could be surmounted by triple inhibitions to TRK, EGFR, and ERK.